Neuropsychological, neurological and functional outcome following pallidotomy for Parkinson's disease. A consecutive series of eight simultaneous bilateral and twelve unilateral procedures. - Scott, R; Gregory, R; Hines, N; Carroll, C; Hyman, N; Papanasstasiou, V; Leather, C; Rowe, J; Silburn, P; Aziz, T (1998)
Intellectual, psychological and functional outcomes were evaluated in a consecutive series of 20 Parkinsonian patients who had unilateral (UPVP) or simultaneous bilateral posteroventral pallidotomy (BPVP) using Image Fusion and Stereoplan (Radionics Inc., Boston, Mass., USA) with stimulation for lesion localization. Comprehensive baseline and 3-month postoperative neuropsychological and neurological assessment protocols were administered together with questionnaire measures of functional disability, quality of life and psychological symptomatology. Changes in patients' clinical presentation and scores on psychometric tests, questionnaires and observational rating scales were then examined. We observed no new neuropsychiatric sequelae directly related to pallidotomy. Cognitive sequelae were restricted to selective reductions in categorical verbal fluency following UPVP (P < 0.001) and BPVP (P < 0.01) and a reduction in phonemic verbal fluency following BPVP (P < 0.01); these changes were not reported subjectively. A fall in diadochokinetic rates (P < 0.01) and some subjective reports of a worsening in pre-existing dysarthria, hypophonia and hypersalivation/drooling following BPVP also suggested changes in speech motor apparatus; however, these changes did not have significant functional consequences. There was one case of more generalized cognitive impairment following BPVP. We also observed significant symptomatic improvement on neurological rating scales; following UPVP, Total Unified Parkinson's Disease Rating Scale (UPDRS) scores improved by 27% (P < 0.01) and following BPVP the improvement was 53% (P < 0.05). Patients' perceptions of reduced postoperative functional disability and improvements in 'quality of life' also achieved statistical significance on a number of both physical and psychosocial questionnaire subscales.